ASUHAN KEPERAWATAN PADA PASIEN OPEN DEGLOVING FEMUR DEXTRA DENGAN PEMBERIAN INTERVENSI TERAPI KOGNITIF TERHADAP PENINGKATAN HARGA DIRI DI RUANG ANGGREK C RSUD KABUPATEN TANGERANG - Afrina Kusuma Dewi; Cicirosnita J. Idu; Ahmad Hambali (Nusantara Hasana Journal, 2024)
Patients with open degloving dextra femur who underwent long treatment in hospital experienced low self-esteem characterized by negative selfassessment, feeling embarrassed, and rejecting positive assessments about themselves. Based on the data obtained, this degloving is a very rare case in the Anggrek C Room at Tangerang Regency Regional Hospital, during 2023 there was only 1 case, where this case occurred in October. Objective: Increase patient self-esteem by providing cognitive therapy interventions. Method: A pre-test and post-test were carried out both before and after cognitive therapy was given with the Rosenberg Self Esteem Scale (RSES) instrument which contains 10 statements, each of which has an assessment which will then be added up and categorized. Cognitive therapy is divided into 4 sessions, which the author did for 3 days. Session 1 is identifying negative thoughts that automatically arise. Session 2 is using acceptable responses to negative thoughts that automatically arise. Session 3 explains the benefits of acceptable responses to negative thoughts that automatically arise. Session 4 involves the family as a supporter to help the patient increase his self-esteem. Results: Before giving cognitive therapy, the score was 2 (low self-esteem), but after being given cognitive therapy for 3 days, the score increased to 27 (high self-esteem). In the paired sample t-test, a significance value of 0.023 was obtained, less than the significance level of 0.05, so it can be concluded that cognitive therapy can increase patient self-esteem.